The Assembly of Nonadhesive Fibrinogen Matrices Depends on the αC Regions of the Fibrinogen Molecule - Yermolenko, Ivan S. (American Society for Biochemistry and Molecular Biology, 2012)
Adsorption of fibrinogen on fibrin clots and other surfaces strongly reduces integrin-mediated adhesion of platelets and leukocytes with implications for the surface-mediated control of thrombus growth and blood compatibility of biomaterials. The underlying mechanism of this process is surface-induced aggregation of fibrinogen, resulting in the assembly of a nanoscale multilayered matrix. The matrix is extensible, which makes it incapable of transducing strong mechanical forces via cellular integrins, resulting in insufficient intracellular signaling and weak cell adhesion. To determine the mechanism of the multilayer formation, the physical and adhesive properties of fibrinogen matrices prepared from human plasma fibrinogen (hFg), recombinant normal (rFg), and fibrinogen with the truncated αC regions (FgAα251) were compared. Using atomic force microscopy and force spectroscopy, we show that whereas hFg and rFg generated the matrices with a thickness of ∼8 nm consisting of 7–8 molecular layers, the deposition of FgAα251 was terminated at two layers, indicating that the αC regions are essential for the multilayer formation. The extensibility of the matrix prepared from FgAα251 was 2-fold lower than that formed from hFg and rFg. In agreement with previous findings that cell adhesion inversely correlates with the extensibility of the fibrinogen matrix, the less extensible FgAα251 matrix and matrices generated from human fibrinogen variants lacking the αC regions supported sustained adhesion of leukocytes and platelets. The persistent adhesiveness of matrices formed from fibrinogen derivatives without the αC regions may have implications for conditions in which elevated levels of these molecules are found, including vascular pathologies, diabetes, thrombolytic therapy, and dysfibrinogenemia.